Development of PSS/E Model for Enhanced STATCOM - Götenfelt, Eric; Eriksson, Linus (My University, 2023)
Abstract More and more of the conventional power generation is being replaced by converter based power generation. This increase of converter-based generation will test the power system with new challenges such as lack of inertia, low network strength and limited fault current injection capability. To address these problems a new Flexible AC Transmission System (FACTS) has been developed, the E-STATCOM, which can provide voltage support in the form of reactive power and frequency support in the form of active power and is a further development of the existing STATCOM. To be able to specify and test that the E-STATCOM is behaving as expected in the connected network, it has to be done multiple studies and analyses. One of the ways that is used to test the product is the power system analysis program PSS®E, which allows for system studies on large networks to be carried out and see how the E-STATCOM behaves during different test cases. In order to carry out these studies in PSS®E a model of the E-STATCOM has to be developed in the programming language FORTRAN. In this project the E-STATCOM is modeled in FORTRAN and tested for its behavior during various cases such as a change in active power load and a change in frequency on the network. The modeled E-STATCOM responds with various results on the tested cases however not fully as desired, a suggestion to a possible solution is made on how to make the E-STATCOM behave fully as intended.